Inverse nodal problem for p-Laplacian energy-dependent Sturm-Liouville equation - Koyunbakan, Hikmet (Springeropen, 2013)
In this study, the inverse nodal problem is solved for p-Laplacian Schrodinger equation with energy-dependent potential function with the Dirichlet conditions. Asymptotic estimates of eigenvalues, nodal points and nodal lengths are given by using Prufer substitution. Especially, an explicit formula for a potential function is given by using nodal lengths. Results are more general than the classical p-Laplacian Sturm-Liouville problem. For the proofs, methods previously developed by Law et al. and Wang et al., in 2009 and 2011, respectively, are used. In there, they solved an inverse nodal problem for the classical p-Laplacian Sturm-Liouville equation with eigenparameter boundary conditions.
Keywords: Prufer substitution; inverse nodal problem; p-Laplacian equation